2008
DOI: 10.1080/08870440701405704
|View full text |Cite
|
Sign up to set email alerts
|

The role of motives in exercise participation†

Abstract: The aim was to better understand the role of motives in exercise participation. It was hypothesised that motives influence exercise participation by influencing behavioural regulation, and that motives are themselves influenced by personality traits. Data were from a cross-sectional questionnaire survey of 252 office workers, mean age 40 years. Analysis was by structural equation modelling. According to the final model, appearance/weight motive increased external regulation, thereby reducing participation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
251
3
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(311 citation statements)
references
References 53 publications
25
251
3
16
Order By: Relevance
“…These correlations show that people with different personalities have distinct considerations when it comes to exercising. This is consistent with Ingledew and Markland [22], where they found that different personalities have distinct motivations for change in exercise participation, for instance, Openness positively correlated with a health/fitness motivation. These studies indicate that people with different personalities should be motivated in different ways to participate in exercise and encourage personality-tailored interventions for physical activity (e.g., [43,44]).…”
Section: Introductionsupporting
confidence: 79%
“…These correlations show that people with different personalities have distinct considerations when it comes to exercising. This is consistent with Ingledew and Markland [22], where they found that different personalities have distinct motivations for change in exercise participation, for instance, Openness positively correlated with a health/fitness motivation. These studies indicate that people with different personalities should be motivated in different ways to participate in exercise and encourage personality-tailored interventions for physical activity (e.g., [43,44]).…”
Section: Introductionsupporting
confidence: 79%
“…Athletes reported strong outcome expectancies relevant to health, fitness, and body image; which supports previous physical activity maintenance research among adult office workers [80] and adult women [81]. The current study is among the first to specifically target college-aged athletes' physical activity maintenance.…”
Section: Physical Activity Maintenancesupporting
confidence: 60%
“…These findings complement empirical findings regarding the importance of ID regulation in explaining persistence in strenuous physical activity, a behavior that may not always be inherently enjoyable. [44][45][46] Interestingly, IJ regulation, which tends to be higher in women, has also been associated with engaging in physical activity. 44,47 However, Pelletier and colleagues found that IJ predicted short-term participation in physical activity but not persistence over time.…”
Section: Intensity and Perceived Exertionmentioning
confidence: 99%